Anal Squamous Intraepithelial Lesions (SILs) in Human Immunodeficiency Virus–Positive Men Who Have Sex With Men: Incidence and Risk Factors of SIL and of Progression and Clearance of Low-Grade SILs. (22nd November 2019) - Jongen, V W; Richel, O; Marra, E; Siegenbeek van Heukelom, M L; van Eeden, A; de Vries, H J C; Cairo, I; Prins, J M; Schim van der Loeff, M F
Abstract : Incident low-grade and high-grade anal squamous intraepithelial lesions (SILs) were common during follow-up among human immunodeficiency virus–positive men who have sex with men. Most low-grade SILs seen at baseline regressed spontaneously, and only a small portion progressed. Abstract: Background: Human immunodeficiency virus (HIV)–positive men who have sex with men (MSM) are at risk of anal squamous cell carcinoma. Data are limited on the natural history of the precursor to this carcinoma, anal squamous intraepithelial lesions (SILs). Methods: HIV-positive MSM were screened for histopathological SILs by means of high-resolution anoscopy (HRA). For participants without SILs at baseline, we estimated the cumulative incidence and risk factors for SILs. For those with low-grade SILs (LSILs) at baseline, the risk of progression to high-grade SILs (HSILs) and the clearance rate were estimated at the lesion level. Results: Of 807 men without SILs at baseline, 107 underwent follow-up HRA between 1 to 4.5 years later. At the second visit 18 men (16.8%) showed LSIL, and 25 (23.4%) HSIL. Age was associated with incident LSILs (adjusted odds ratio [aOR], 2.10 per 10-year increase in age; P = .01). Of 393 men with LSILs at baseline, 114 underwent follow-up HRA 0.5 to 2.5 years later. Of the 177 LSILs found at baseline, 87 (49.2%) had cleared at the second visit, and 29 (16.4%) had progressed to HSILs. Conclusion: Incident LSILs and HSILs were common during follow-up among HIV-positive MSM without dysplasia at baseline. Among men with LSILs at baseline, nearly half of these lesions cleared, and a small portion progressed.